Femtosecond time-resolved two-photon photoemission studies of ultrafast carrier relaxation in Cu2O photoelectrodes - Mario Borgwardt (Nature Portfolio, 2019)
While cuprous oxide is a promising solar-to-fuel conversion material, photoelectrochemical devices substantially underperform. Here, the authors use femtosecond time-resolved two-photon photoemission spectroscopy to correlate photoexcited electron energetics and dynamics with performance losses.